2013
DOI: 10.1038/onc.2013.205
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of MyD88 and Mal/TIRAP in TLR2-mediated gastric tumourigenesis

Abstract: Signalling by the toll-like receptor (TLR) family of pathogen recognition receptors has emerged as a key molecular component in the pathogenesis of an increasing number of inflammatory-related cancers, among which gastric cancer rates as the second most lethal cancer world-wide. The myeloid differentiation factor 88 (MyD88) adapter molecule has a critical role in mediating innate immune signalling by members of the TLR and interleukin (IL)-1 families, and has been associated with either pro- or antitumourigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
(63 reference statements)
2
33
0
1
Order By: Relevance
“…6E). We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…6E). We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24).…”
Section: Discussionsupporting
confidence: 62%
“…F/F mice, in which hyperactivation of Stat3 promotes gastric tumorigenesis via the TLR2/MyD88 cascade (19,28,29). The expression levels of Tnf, Cd14, Casp1, Il1a, and Tlr2 were significantly increased in gp130 F/F tumors; however, this upregulation was not suppressed in the gp130 F/F Myd88 À/À mouse tumors, in which Myd88 was disrupted in both epithelial and stromal cells ( Supplementary Fig.…”
Section: The Suppression Of the Inflammatory Responses In Gan Myd88mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, autosomal recessive deficiencies of IRAK1 and MYD88 impair Toll-like receptor (TLR) to recurrent life-threatening bacterial diseases [59]. TIRAP is dispensable in TLR2 signalling at high ligand concentrations in macrophages and dendritic cells, with MyD88 probably coupling to the TLR2 receptor complex at sufficient levels to allow activation but having an inhibitory role in the signalling of TLR3 to JNK [60,61]. Although these results need to be validated through experimental investigation, they represent a promising direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The normal samples were classed as the controls and the normalized data were analyzed using a t-test (20,21) implemented in LIMMA package (22). The differential genes in the metastatic and non-metastatic OS samples were considered to be those with a P-value <0.05.…”
Section: Methodsmentioning
confidence: 99%